2021
DOI: 10.3389/fnins.2021.644757
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Age and Sex in a Mouse Model of Childhood Narcolepsy

Abstract: Narcolepsy is a sleep disorder caused by selective death of the orexin neurons that often begins in childhood. Orexin neuron loss disinhibits REM sleep during the active period and produces cataplexy, episodes of paralysis during wakefulness. Cataplexy is often worse when narcolepsy develops in children compared to adults, but the reason for this difference remains unknown. We used orexin-tTA; TetO DTA mice to model narcolepsy at different ages. When doxycycline is removed from the diet, the orexin neurons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 71 publications
4
16
2
Order By: Relevance
“… 19 , 41 Won et al found that females are less likely to report lifestyle impairments in the areas of personal relationships and physical activity compared to males in spite of being objectively sleepier; however both patients with narcolepsy with and without cataplexy were involved in this study. 41 Recent studies reported that in narcolepsy mouse models, females have larger number of cataplexy bouts 42 and increased wake 43 compared to males, with unclear findings in humans with narcolepsy. 19 , 41 Our result of sex differences in narcolepsy diagnostic delay in adults suggest that social factors (eg, different roles of males/females in their households and employment) may play an important role in narcolepsy diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 41 Won et al found that females are less likely to report lifestyle impairments in the areas of personal relationships and physical activity compared to males in spite of being objectively sleepier; however both patients with narcolepsy with and without cataplexy were involved in this study. 41 Recent studies reported that in narcolepsy mouse models, females have larger number of cataplexy bouts 42 and increased wake 43 compared to males, with unclear findings in humans with narcolepsy. 19 , 41 Our result of sex differences in narcolepsy diagnostic delay in adults suggest that social factors (eg, different roles of males/females in their households and employment) may play an important role in narcolepsy diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the consequences of dietary DOX withdrawal and subsequent Hcrt neuron degeneration has been well-documented in male orexin-tTA; TetO DTA mice 30 , similar information for female mice of this strain has been lacking. This is not unusual as, with some notable exceptions [35][36][37][38][39][40][41][42] , female mice have been rarely used in sleep studies 27,43 . The primary symptoms of human narcolepsy that can be assessed in a mouse model of this disorder are excessive daytime sleepiness (EDS), nocturnal sleep disruption and cataplexy, the pathognomonic symptom of NT1.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, FAA was attenuated in orexin KO mice but not eliminated, and core body temperatures and food consumption in the orexin KO mice and control mice were similar ( Kaur et al, 2008 ). Research also demonstrated that KO of the orexin system results in narcolepsy and sleep fragmentation ( Coffey et al, 2021 ). These results suggest that orexin neurons may sense the metabolic status and modulate arousal to promote food-seeking behavior during RF regimes.…”
Section: Discussionmentioning
confidence: 99%